2012
DOI: 10.1080/00049182.2012.731302
|View full text |Cite
|
Sign up to set email alerts
|

Placing Bets: gambling venues and the distribution of harm

Abstract: The liberalisation of gambling in Australia has resulted in the dispersal of 200 000 electronic gaming machines (EGMs) across the country, generating substantial revenues for State governments and the gambling industry as well as causing significant gambling-related harm. While the spatial distribution of EGM venues has been shown to follow a gradient of community disadvantage, little is known about the distinctions between the venues themselves (i.e. pubs, clubs, and casinos), either in terms of the catchment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 30 publications
3
29
0
Order By: Relevance
“…First, gambling venues in this study were predominantly located in low socio-economic areas, a finding that is consistent with trends reported in both the Australian (Young et al, 2012a;McMillen & Doran, 2006) and international literature (Pearce, Mason, Hiscock, & Day, 2008;Wheeler, Rigby, & Huriwai, 2006). This poses a significant challenge for public health authorities given the harms associated with gambling for vulnerable populations, including those from low socioeconomic backgrounds (Welte, Wieczorek, Barnes, Tidwell, & Hoffman, 2004;Welte, Wieczorek, Barnes, & Tidwell, 2006).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…First, gambling venues in this study were predominantly located in low socio-economic areas, a finding that is consistent with trends reported in both the Australian (Young et al, 2012a;McMillen & Doran, 2006) and international literature (Pearce, Mason, Hiscock, & Day, 2008;Wheeler, Rigby, & Huriwai, 2006). This poses a significant challenge for public health authorities given the harms associated with gambling for vulnerable populations, including those from low socioeconomic backgrounds (Welte, Wieczorek, Barnes, Tidwell, & Hoffman, 2004;Welte, Wieczorek, Barnes, & Tidwell, 2006).…”
Section: Discussionsupporting
confidence: 76%
“…While significant research has focused on the role of individual pathology in the manifestation of problem gambling (Blaszczynski, Ladouceur, & Shaffer, 2004), much less has focused on industry tactics (Thomas, Lewis, McLeod, & Haycock, 2012), product designs (Dow-Schüll, 2012), and gambling environments (e.g. the clustering of gambling products and marketing for these products in specific environments) (Lindsay et al, 2013;Young, Markham, & Doran, 2012a). We know of no research to date that comprehensively considers how these factors work both independently and together to create and perpetuate problem gambling in communities.…”
Section: Problem Gambling In Australiamentioning
confidence: 99%
“…However, less is known about the relationship between type of venue, venue characteristics, and gambling behavior (Hing & Haw, 2010;Young et al, 2012). As all gambling venues differ, the individual has the opportunity to choose to gamble in a multitude of different settings, such as casinos, bingo halls, arcades, betting shops, clubs, and pubs.…”
Section: Introductionmentioning
confidence: 99%
“…We included other licensing variables, such as venue type (i.e. hotel, club or casino) and the number of operational EGMs, as covariates as previous studies have shown these to be associated with rates of gambling-related harm [21]. All statistical analyses were determined prior to commencing analysis except for post-stratification weighting, which was conducted following the suggestion of an anonymous reviewer.…”
Section: Discussionmentioning
confidence: 99%
“…First, as the site at which most gambling actually occurs in developed countries, regulated gambling venues provide arguably the most important location at which harm minimization interventions can be targeted. Levels of harm among patrons vary between venues [21,22], suggesting that venue-specific factors may play a substantial role in mediating the riskiness of gambling. Secondly, an emerging body of literature has documented a relationship between heightened problem gambling risk and residential distance to gambling venues at the level of the individual gambler [23][24][25].…”
Section: Literature Reviewmentioning
confidence: 99%